(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The 1997-2000 Iranian reform movement commonly known as the civil rights movement, is a crucial but poorly investigated time in the history of Iranian women politics. Although the literature has developed heavily on the status of women under the Pahlavi dynasty and the early Islamic Republic, little has been done to offer a review on the tremendous political gains women had made during the presidency of Mohammad Khatami. This paper attempts to fill this gap by writing and examining the most significant political involvement of Iranian women in the period between 1997 and 2000. The paper cites election records, NGO statistics, legislative analysis, and women periodicals to show that, during this period, women had made significant political gains: 297 women were elected to city councils and 484 to rural councils in 1999, with women leading the vote in 56 cities, women topping the vote in 300 cities; almost 1,000 women had been appointed to executive posts, including three presidential advisors, 16 ministerial advisors, and 105 Directors General; and women NGO Laws also made progress, whereby marriage age was increased, more rights of divorce and property rights were also acknowledged to the female. Nevertheless, enduring constraints are also reported in the paper: by the year 2000, only 3 percent of high-level jobs were occupied by women, opposition by hardliners shut down feminist magazines, and institutionalized discrimination persisted in inheritance rules, judicial testifying, and judgeship appointments. The paper claims that such gains came on the basis of strategic mobilization of women as voters, lobbyists, and candidates challenging the narratives that depict Iranian women as passive receivers of state policy.